Mechanism, clinical manifestations, prevention, and treatment of air embolism during ERCP - CHEN Junzong, LIU Kai, TANG Di (Waike lilun yu shijian)
Endoscopic retrograde cholangiopancreatography (ERCP) is a pivotal endoscopic technique for hepatobiliary and pancreatic diseases. Although rare, air embolism during ERCP carries a high risk of mortality and disability, with significant challenges in timely recognition. Current understanding of its pathogenesis, clinical manifestations, and emergency management remains insufficient. Air embolism requires two prerequisites: an open vascular pathway​and abnormal pressure gradients. It can be classified into venous, arterial, and paradoxical​subtypes based on the embolized vasculature. Clinical presentations are nonspecific and heterogeneous, often​masked by sedation or anesthesia, leading to delayed diagnosis. Key risk factors include prior biliary surgery, sphincterotomy, biliovenous fistula formation, and biliary stent placement. Diagnosis relies on integrating intraoperative vital sign monitoring, imaging​examination, and ​cardiocirculatory/neurological assessments. Timely recognition and intervention are critical, including​procedure termination, 100% oxygen therapy, positional adjustment, and hemodynamic stabilization. Preventive strategies involve strict adherence to ERCP indications, preoperative screening of high-risk patients, CO₂ insufflation ​instead of air, and ​enhanced intraoperative real-time monitoring. Clinicians should maintain a high alert for air embolism, optimize procedural protocols, implement surveillance, and establish emergency response plans ​to mitigate this life-threatening complication.